PENGARUH GREEN ACCOUNTING, KINERJA LINGKUNGAN, DAN WOMAN ON BOARD TERHADAP NILAI PERUSAHAAN - Zega, Yesica Cahayani Kristina; Angela, Aurora (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
This study is based on the increasing popularity of environmental problems and equal treatment for women, as well as the importance of non-financial information disclosure in improving corporate value.  This study will look at the impact of green accounting, environmental performance, and women on boards on firm value in the energy industry listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023, 84 research data samples were obtained. Multiple linear regression was used to examine the impact of the variables green accounting, environmental performance, and women on board on the value of the company. The findings indicated that while green accounting and having women on board had no discernible impact on firm value, environmental performance did. Although the adoption of green accounting and the presence of women on the board of directors have had a significant impact on raising company value, this research suggests that investors and the general public have greater trust in businesses that perform well in terms of the environment. This study has significant ramifications for businesses looking to improve inclusive governance and increase environmental transparency.